2016
DOI: 10.1007/s11356-016-7991-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of predicted aquatic risks of pesticides used under different rice-farming strategies in the Mekong Delta, Vietnam

Abstract: This study evaluates the risks of pesticides applied in rice-fish and rice farming, with and without integrated pest management (IPM) strategies, to non-target aquatic organisms in two provinces of the Mekong Delta, Vietnam. Pesticide inventories and application patterns were collected from 120 Vietnamese farmers through interviews. Risks were assessed using (1) Pesticide RIsks in the Tropics to Man, Environment, and Trade (PRIMET), a first-tier model, which calculates predicted environmental concentrations (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 38 publications
0
16
1
2
Order By: Relevance
“…The concentration of diazinon in rice in the present study was dramatically lower than diazinon in rice farming (58.4 ng g −1 ) and rice-fish farming paddies (117 ng g −1 ) from Can Tho, Vietnam [39]. The average of diazinon in rice samples (31.9 mg/kg) from Anzali International Wetland basin, Iran [40] was far higher than the present study.…”
Section: Presence Of Opps In Paddy Rice and Soilcontrasting
confidence: 75%
“…The concentration of diazinon in rice in the present study was dramatically lower than diazinon in rice farming (58.4 ng g −1 ) and rice-fish farming paddies (117 ng g −1 ) from Can Tho, Vietnam [39]. The average of diazinon in rice samples (31.9 mg/kg) from Anzali International Wetland basin, Iran [40] was far higher than the present study.…”
Section: Presence Of Opps In Paddy Rice and Soilcontrasting
confidence: 75%
“…These target pesticides were demonstrated that they are more susceptible to alkaline hydrolysis and highly degradable in the neutral to basic conditions [33,34]. They are able to accumulate as existing in natural environment, harm to aquatic organisms and ecosystems or cause negative effects to the environment [35][36][37].…”
Section: Properties Of Wastewater and Target Pesticidesmentioning
confidence: 99%
“…Also, pesticides affect non-target organisms in the aquatic and terrestrial ecosystems [6,7,8]. In the wetland agro-ecosystems, pesticides affect nontarget organisms through undesirable exposures to contaminants in water bodies, runoffs, and spray drift [9]. Lately, the chances of pesticide contamination in the Ndop flood plain of Cameroon are very high since crop cultivation has become very intensive to meet the urban food demands.…”
Section: Introductionmentioning
confidence: 99%